Model-Model Kurikulum Bahasa Arab di Pesantren Indonesia Tinjauan Literatur Sistematis 2020–2025 - Hanifa, Zahra Aulia; Ali, Mad (Journal of Islamic Education El Madani, 2025)
This study aims to systematically examine the various Arabic language curriculum models implemented across different types of Islamic boarding schools (pesantren) in Indonesia during the period 2020–2025. This review is significant considering the evolving educational landscape of pesantren, which are increasingly responding to the demands of 21st-century learning while preserving their distinctive Islamic traditions. A Systematic Literature Review (SLR) method was employed, analyzing ten accredited scholarly articles relevant to the topic. The findings reveal a diversity of curriculum models, including the Merdeka Curriculum, the 2013 Curriculum, Kulliyyatu al-Mu’allimîn al-Islâmiyyah, traditional salafiyah curricula, integrated curricula, and humanistic approaches. Among these, the integrative curriculum emerged as the most promising model, effectively bridging Islamic values, national education standards, and 21st-century competencies. The study concludes that Arabic curriculum transformation in pesantren is moving towards a synthesis of tradition and pedagogical innovation. The implications suggest the need for strategic collaboration among Islamic boarding schools, educational scholars, and policymakers to develop adaptive, contextual, and sustainable curricula, supported by improved teacher training and learning infrastructure.